Transition readiness among finnish adolescents with juvenile idiopathic arthritis - Katriina Mikola; Katariina Rebane; Hannu Kautiainen; Kristiina Aalto (Pediatric Rheumatology Online Journal, 2023)
Abstract Background With chronic diseases, the responsibility for care transfers to adult clinics at some point. Juvenile idiopathic arthritis (JIA) is the most common persistent rheumatic condition in children. A successful transition requires sufficient self-management skills to manage one´s chronic condition and all the tasks involved. In this study, we evaluated transition readiness in Finnish patients with JIA. We aimed to find practical tools to support a successful transition and to study the possible consequences of an unsuccessful transition. Methods The usefulness of a specific questionnaire, which was administered to 83 JIA patients, was evaluated in this study. We also gathered information from their first adult clinic visit to assess the success of their transition and its relation to disease activity. Results In 55 (71%) patients, the transition was estimated to be successful. We were able to determine a cut-off score in the questionnaire for a successful transition: the best estimate for a successful transition is when the score is 24 or more. At the first adult clinic visit, an unsuccessful transition was evident in its effect on disease outcome. If the transition was defined as successful, the DAS28 was better. Conclusion We found the questionnaire to be a useful tool for evaluating transition readiness. Determination of a successful transition helped us identify those adolescents who needed more profound support to improve their self-management skills and thus enhance their transition process. An unsuccessful transition was shown to negatively impact on disease outcomes.